A Bat-inspired Strategy for Pairwise Testing - Alsariera, Yazan A.; Mazlina, Abdul Majid; Kamal Z., Zamli (ARPN, 2015)
Owing to exponential growth of software lines of codes (LOC)s, testing becomes painstakingly difficult activities. Test engineers are often under pressure to test more and more LOCs yet within the same targeted deadline. For this reason, efficient testing strategy is required. Pairwise testing is amongst the most common strategies for minimizing and sampling of tests for testing consideration. Recently, there are growing interests for adapting optimization algorithms as the basis of the newly developed strategies. Complementing the existing work, we propose a novel design and implementation of Bat-inspired algorithm (BA) for pairwise strategy, called Bat-inspired pairwise testing strategy (BPTS). Based on the benchmarking results, BPTS outperforms most existing strategies in terms of the generated test suite size. BPTS serves as our research vehicle to investigate the effectiveness of Bat-inspired algorithm for pairwise test generation, which is going to be helpful to reduce the time and cost of software testing by reducing the number of test cases.